Ethnic Identity and Local Politics: Study on Regional Head Election in Merauke Regency 2020 - Misran Alfarabi; Wahdania Suardi; Zuly Qodir (Universitas Muhammadiyah Tangerang, 2021)
In the Regional Head Election of Merauke Regency, there was a contestation between tribes to win the candidate. In this contestation, there was a conflict between ethnic groups, namely the indigenous Papuans and migrants. This study aims to discuss the political struggle of the Merauke Regency to get political support through entities. This study uses an analytical approach to research from several emerging factors such as ethnicity. Data collection was obtained from online media reporting writers, interview websites, and research reports. This study found that identity cannot be separated in the Merauke district, where politics is considered to have its positives and negatives. The positive is to ensure that ethnic immigrants in the Merauke district respect indigenous peoples as owners of territory. The negative is that there is no right to become regent for the immigrant tribes in the Merauke district even though they have fulfilled the requirements as a leader. There are no rules regarding who has the right to lead in special autonomy in the Papua region. This case raises many things related to Papuans in Indonesia in particular.Pada Pemilihan Kepala daerah Kabupaten Merauke terjadi kontestasi antar suku untuk memenangkan kandidatnya. Pada kontestasi ini terjadi konflik antar suku yaitu suku asli papua dan suku pendatang Penelitian ini bertujuan membahas pertarungan politik kabupaten Merauke untuk mendapatkan dukungan politik melaui entnisitas. Penelitian ini menggunakan pendekatan kualitatif dengan penelitian analitis dari beberapa factor yang muncul seperti etnisitas. Pengumpulan data diperoleh penulis dari pemberitaan media online, website wawancara, dan laporan riset. Penelitian ini menemukan identitas tidak dapat terlepas di kabupaten Merauke dengan politik dianggap memiliki positif dan negatifnya. Positifnya adalah memastikan bahwa suku pendatang yang berada di kabupaten Merauke menghargai masyarakat adat sebagai pemilik atas wilayah. Negatifnya adalah tidak adanya hak untuk menjadi bupati bagi suku pendatang yang ada dikabupaten Merauke meskipun telah memenuhi syarat sebagai seorang pemimpin. Tidak adanya aturan terkait siapa yang berhak memimpin dalam otonomi khusus di wilayah papua. Kasus ini memunculkan banyak penafsiran terkait kekhususan orang-orang papua di Indonesia.